A Reversible Electron Relay to Exclude Sacrificial Electron Donors in the Photocatalytic Oxygen Atom Transfer Reaction with O2 in Water. Issue 45 (25th September 2019) - Vo, Nhat Tam; Mekmouche, Yasmina; Tron, Thierry; Guillot, Régis; Banse, Frédéric; Halime, Zakaria; Sircoglou, Marie; Leibl, Winfried; Aukauloo, Ally
Abstract: Using light energy and O2 for the direct chemical oxidation of organic substrates is a major challenge. A limitation is the use of sacrificial electron donors to activate O2 by reductive quenching of the photosensitizer, generating undesirable side products. A reversible electron acceptor, methyl viologen, can act as electron shuttle to oxidatively quench the photosensitizer, [Ru(bpy)3 ] 2+, generating the highly oxidized chromophore and the powerful reductant methyl‐viologen radical MV +. . MV +. can then reduce an iron(III) catalyst to the iron(II) form and concomitantly O2 to O2 .− in an aqueous medium to generate an active iron(III)‐(hydro)peroxo species. The oxidized photosensitizer is reset to its ground state by oxidizing an alkene substrate to an alkenyl radical cation. Closing the loop, the reaction of the iron reactive intermediate with the substrate or its radical cation leads to the formation of two oxygenated compounds, the diol and the aldehyde following two different pathways. Abstract : The evil necessity of sacrificial electron donors (SEDs) in the photoactivation of O2 can be ousted by the use of a reversible electron acceptor (methylviologen). It intervenes as an electron carrier from the excited photosensitizer to reduce both O2 and an iron(III) catalyst to form a reactive Fe III –peroxo species for oxygen atom transfer reactions. Oxidation of an organic substrate closes the photocatalytic cycle.